Implementation of Internet Financial Reporting to Increasing Accountability in Zakat Management Organizations: Based on PSAK No. 109 - Suhaidar, Suhaidar; Anggita, Wenni; Karmawan, Karmawan; Rudianto, Nur Ahmad Ricky (Integrated Journal of Business and Economics (IJBE), 2021)
The report of the Zakat Organization Forum (FOZ) states that one of the factors in the weak ability of OPZ in managing national zakat funds is the lack of transparency of zakat managers regarding the publication of the results of collections and other Islamic philanthropic funds. So, the purpose of this research is to see the extent of implementation of internet financial reportring to incresing accountability in zakat management organizations.  The method used in this study is  descriptive qualitative, with a sample of 11 OPZ who did internet financial reporting in 2017 and 2018. The results of the study revealed that internet financial reporting of OPZ was in the middle category level with a value of 60.13%. This indicates that the level of disclosure of internet financial reporting in Indonesia is still not good because it is still at the intermediate level. This happens because the prevailing regulations are still weak and there has been no action from the government in regulating OPZ financial reporting because OPZ itself is still in the form of non-profit organizations.